(untitled) (EU and comparative law issues and challenges series (ECLIC), 2018)
The legal rules in the Republic of Macedonia regarding cross border recovery of maintenance have been more or less unchanged from the Yugoslav Act Concerning the Resolution of Conflicts of Laws with Provisions of Other States in Certain Matters (PIL act of 1982). This means that most of the jurisdictional rules and the conflict of law rules are now turning 35 years. Meanwhile the Hague Conference of Private International Law has provided for two new legal acts, the 2007 Convention on the International Recovery of Child Support and Other Forms of Family Maintenance and the 2007 Hague Protocol on the Law Applicable to Maintenance Obligations which introduce new conflict of law rules regarding maintenance obligations. Moreover, the EU has adapted a new Council Regulation (EC) No 4/2009 of 18 December 2008 on jurisdiction, applicable law, recognition and enforcement of decisions and cooperation in matters relating to maintenance obligations. In this context the Republic of Macedonia (as a EU candidate country) now faces contemporary challenges to adjust its legal system to the new jurisdictional criteria and conflict of law rules developed by the Hague Conference of Private International Law and the EU. This article firstly gives a brief overview of the current PIL rules regarding recovery of maintenance in the Republic of Macedonia, comparing them to the rules provided in the 2007 Hague Protocol and the Maintenance Regulation and secondly it will address the means of the adjustment of such rules in the Republic of Macedonia.